Bone health of female elite cyclists is characterized by impaired cortical and trabecular microarchitecture - Hilkens, L.; Bevers, M. S. A. M.; Wyers, C. E.; Van Loon, L. J. C.; Van den Bergh, J. P.; Van Dijk, J.-W. (Medicine & Science in Sports & Exercise, 2025)
Purpose Many elite road-race cyclists have low areal bone mineral density (aBMD) as previously shown by dual-energy x-ray absorptiometry (DXA). However, aBMD provides limited insight into bone quality. Therefore, this cross-sectional study aimed to assess volumetric BMD (vBMD), bone microarchitecture, and bone strength in elite road-race cyclists using high-resolution peripheral computed tomography (HR-pQCT), along with aBMD measured by DXA.